1991
DOI: 10.2307/2937196
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Density, Stage, and Patchiness in the Transmission of an Insect Virus

Abstract: Although the importance of insect viruses in the population dynamics of their hosts is widely acknowledged, ecologists are still relatively ignorant of the factors determining the rate of transmission of insect viruses in the field. I performed a series of field experiments in which I investigated the transmission dynamics of the nuclear poly— hedrosis virus (NPV) of Douglas—fir tussock moth, Orgyia pseudotsugata (Lepidoptera: Lymantriidae), in northern Idaho, USA. In these experiments, I reared healthy and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
115
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 57 publications
2
115
0
1
Order By: Relevance
“…By adding an explicit heterogeneity term to the standard transmission model, Dwyer et al (1997) showed that increasing the degree of heterogeneity among the host population leads to an increase in the degree of non-linearity in the transmission rate. Furthermore, Dwyer et al (1997) showed that the heterogeneity model fitted the observed transmission rates better than the simple homogeneous model, attributing the heterogeneity to inherent variations in susceptibility among the hosts, including differences in susceptibility between instars (Dwyer 1991). However, such heterogeneities may also arise through an environmental or spatial factor which results in some hosts being more at risk of contacting the parasites than others (Knell et al 1996(Knell et al , 1998a.…”
Section: Discussionmentioning
confidence: 99%
“…By adding an explicit heterogeneity term to the standard transmission model, Dwyer et al (1997) showed that increasing the degree of heterogeneity among the host population leads to an increase in the degree of non-linearity in the transmission rate. Furthermore, Dwyer et al (1997) showed that the heterogeneity model fitted the observed transmission rates better than the simple homogeneous model, attributing the heterogeneity to inherent variations in susceptibility among the hosts, including differences in susceptibility between instars (Dwyer 1991). However, such heterogeneities may also arise through an environmental or spatial factor which results in some hosts being more at risk of contacting the parasites than others (Knell et al 1996(Knell et al , 1998a.…”
Section: Discussionmentioning
confidence: 99%
“…Nothing is known about fue ability of fue novel (third) virus to cause patent infections in blackflies. The role of spatial heterogeneity in fue distribution of larvae was not addressed here but mar be an additional factor of imporlance in fue dynamics of fue host-pathogen interaction as reported in other insect virus systems (Dwyer 1991). The bioassay procedures used were highIy sensitive.…”
Section: Discussionunclassified
“…Evidence for effects of such large-scale mechanisms on the transmission of this or other baculoviruses, however, is almost entirely lacking (D' Amico and Elkinton, 1995;Dwyer, 1991). More-393 over, failed efforts to estimate the decay rate µ experimentally suggest that µ may be very low for this virus (Dwyer (1991), Online Appendices).…”
mentioning
confidence: 99%
“…The total time in the m exposed classes is the sum of m such distributions, and a well-known theorem has shown that the sum follows a gamma distri-180 bution with mean, 1/δ, and variance, 1/(mδ 2 ) (Keeling and Rohani, 2008). For the tussock moth virus, the variance in the speed of kill is quite low (Dwyer (1991), also Online Appendices), so in practice we fixed m = 200, rather than estimating m from the observational data.…”
mentioning
confidence: 99%
See 1 more Smart Citation